Transformation of Islamic Religious Education Learning in the Digital Era: A Systematic Literature Review - Dimas Wahyu Ramadhan (Values: Jurnal Kajian Islam Multidisiplin, 2026)
The rapid advancement of digital technology has significantly transformed educational systems, including Islamic Religious Education (IRE) learning. The transformation of IRE extends beyond the integration of technology as a learning medium to encompass changes in instructional strategies, teaching methods, educators' roles, and interactions between teachers and students. This study aims to identify, analyze, and synthesize previous research on the transformation of Islamic Religious Education learning in the digital era through a Systematic Literature Review (SLR). The study adopts the PRISMA guidelines, including the stages of identification, screening, eligibility assessment, and inclusion of scientific articles published between 2020 and 2025 from various academic databases. The findings indicate that the transformation of IRE learning is characterized by the implementation of Learning Management Systems (LMS), digital learning media, online learning platforms, Artificial Intelligence (AI), and student-centered learning approaches. These innovations enhance learning flexibility, student engagement, and access to educational resources. However, challenges remain, including limited digital literacy, unequal technological infrastructure, and the need to strengthen pedagogical competencies and digital ethics among educators and learners. This study concludes that the transformation of Islamic Religious Education in the digital era is an ongoing process that requires the integration of technological innovation, educators' digital competence, and Islamic values to ensure effective, adaptive, and character-oriented learning.